THE USE OF GIST STRATEGY IN READING COMPREHENSION - Mekawati, Agnes Budi Tyas; Tri W, Ch. Evy (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
The objectives of the research are as follows : (1) To know whether using GIST strategy can improve the reading comprehension at the eighth grade students of SMP Saverius Sragen in the Academic Year of 2019/2020. (2) To know how far the implementation of GIST strategy in teaching and learning reading in narrative text at the eighth grade students of SMP Saverius Sragen in Academic Year 2019/2020. The researcher conducted a Classroom Action Research at the eighth grade students of SMP Saverius Sragen from January to February 2020. The subject of the research was the students of VIII A which consisted of 20 students. The research was concerned on improving studentsâ€Ÿ reading comprehension using GIST strategy. It consisted of 2 cycles. Each cycle consisted of two meetings which was 80 minutes for each meeting and every cycle ended by post test. Each cycle had four steps: planning, action, observation and reflection. In collecting the data, the researcher used observation, interview, documentation, and tests(pre-test and post-test). The result of cycle 1 showed that some students had lack of vocabulary and also still had difficulties in finding the main idea, the implicit information and the meaning of difficult words in a text. Therefore, cycle 2 showed that the use of GIST strategy for students had lack of vocabulary and difficulties in finding the main idea could improve the studentsâ€Ÿ reading comprehension. The studentsâ€Ÿ mean score in pre-test was 50.25, post-test I was 66.75, and post-test II 76.80. Based on the result of the research, it could be concluded that â€œThe use GIST (Generating Interaction between Schema and Text) strategy can improve studentsâ€Ÿ reading comprehension in narrative text at the eighth grade students of SMP Saverius Sragen in 2019/2020 academic year especially in class VIII-Aâ€. Key word: Reading Comprehension, GIST Strategy, Classroom Action Research.